Prevalence of and Associations With Distress and Professional Burnout Among Otolaryngologists: Part I, Trainees. (29th September 2020) - Larson, David P.; Carlson, Matthew L.; Lohse, Christine M.; O'Brien, Erin K.; Kircher, Matthew L.; Gurgel, Richard K.; Hunter, Jacob B.; Micco, Alan G.; Nogan, Stephen J.; O'Connell, Brendan P.; Rangarajan, Sanjeet V.; Rivas, Alejandro; et al.
Abstract : Objective: To assess the prevalence of distress and burnout in otolaryngology trainees, including associations with relevant sociodemographic and professional factors, and to compare these results with those of attending otolaryngologists. Study Design: A cross‐sectional survey of trainees and attending physicians. Setting: Twelve academic otolaryngology programs. Methods: Distress and burnout were measured with the Expanded Physician Well‐being Index and the 2‐item Maslach Burnout Inventory. The Patient Health Questionnaire–2 and Generalized Anxiety Disorder–2 were used to screen for depressive disorders and anxiety disorders, respectively. Associations with sociodemographic and professional characteristics were assessed. Results: Of the 613 surveys administered to trainees and attending physicians, 340 were completed (56%). Among 154 trainees, distress was present in 49%, professional burnout in 35%, positive depressive disorder screening in 5%, and positive anxiety disorder screening in 16%. In univariable analysis, female gender, hours worked in a typical week (HW), and nights on call in a typical week (NOC) were significantly associated with distress. In multivariable analysis, female gender (odds ratio, 3.91; P =. 001) and HW (odds ratio for each 10 HW, 1.89; P =. 003) remained significantly associated with distress. Female gender, HW, and NOC were significantly associated with burnout univariably, although only HW (odds ratio for each 10 HW, 1.92; P =. 003) remained significantly associated with burnout in a multivariable setting. Attending physicians had less distress than trainees ( P =. 02) and felt less callous and less emotionally hardened than trainees ( P <. 001). Conclusion: Otolaryngology trainees experience significant work‐place distress (49%) and burnout (35%). Gender, HW, and NOC had the strongest associations with distress and burnout.